2012
DOI: 10.1029/2012rg000392
|View full text |Cite
|
Sign up to set email alerts
|

Modeling morphodynamic processes in meandering rivers with spatial width variations

Abstract: .[1] Most morphodynamic models of river meandering assume spatially constant width; depending on the intensity of spatial width variations, different meandering styles actually exist, often associated with midchannel bars and islands. When intense enough, width oscillations characterize transitional planforms between meandering and braiding. We investigate, on a modeling basis, morphodynamic feedbacks between spatial curvature and width oscillations in river meanders and related bedform patterns. Our review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 113 publications
(225 reference statements)
4
69
0
Order By: Relevance
“…As the chute channel widened and the main channel closed, a stable bifurcation formed with k > 5/3. These findings show that the development of the two types of cutoffs are controlled by different mechanisms (in agreement with Zolezzi et al, 2012;Grenfell et al, In press). Gradient advantage affected the development of the bend cutoff more than the scroll slough cutoff (Table 4).…”
Section: Bend Cutoffsupporting
confidence: 79%
See 2 more Smart Citations
“…As the chute channel widened and the main channel closed, a stable bifurcation formed with k > 5/3. These findings show that the development of the two types of cutoffs are controlled by different mechanisms (in agreement with Zolezzi et al, 2012;Grenfell et al, In press). Gradient advantage affected the development of the bend cutoff more than the scroll slough cutoff (Table 4).…”
Section: Bend Cutoffsupporting
confidence: 79%
“…The process of chute cutoffs has been associated with the transition from a meandering to a braiding style (Ashmore, 1991;Kleinhans and van den Berg, 2011;Zolezzi et al, 2012) because the frequent occurrence of cutoffs render a river multichannel and weakly braided by definition and because chute cutoffs are also frequently observed in braided rivers contrary to neck cutoffs. Furthermore, chute cutoffs limit bend growth and channel sinuosity much more severely than neck cutoff, which only occurs in highly sinuous rivers (Howard, 1996).…”
Section: Chute Cutoffs As An Aspect Of River Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, bed forms (ripples, dunes, and antidunes) [ Blom and Parker , ], multiple‐row bars [ Fujita , ; Schuurman et al ., ], braiding [ Kasprak et al ., ], and meandering [ Asahi et al ., ] are dynamic components that add complexity to the problem of tracer dispersal. Corresponding static components include curvature‐induced forced bars [ Blondeaux and Seminara , ], midchannel bars driven by channel width variation [ Zolezzi et al ., ], and floodplains occasionally accessed by the flow [ Lauer and Parker , ]. Interactions among components of dynamic bed evolution at different spatial and temporal scales can result in a complex pattern of bed surface elevation variability, and static components can serve to store large amounts of sediment.…”
Section: Discussionmentioning
confidence: 99%
“…Meander migration models further assume that the channel width remains constant in space and time, implying that the lateral channel shift is governed by bank erosion and that opposite bank accretion occurs at the same rate. Zolezzi et al (2012) analysed the effects of channel width variations in phase with the channel curvature and found that width variations enhance river bed dynamics.…”
Section: Introductionmentioning
confidence: 99%